Size Optimization of Cooperative Robots for High Flexibility in Target Space - Yuanyuan Li; Xiangquan Liu; Fei Ma (Jixie chuandong)
In order to improve the flexibility of cooperative robots to avoid real-time obstacles in target space， a comprehensive optimization index is proposed， and the size of its key members is optimized. Firstly， the kinematics of the optimized cooperative robot is analyzed， the mathematical model is established， and the reachable workspace is solved； then the target space is selected with the robot's task path as the reference， the flexibility comprehensive evaluation index is defined as the optimization goal， and the particle swarm algorithm is used to optimize the key size parameters； finally， the distribution of flexible working points in the task space before and after optimization is compared. The results show the proportion of flexible working points of the optimized robot increases significantly， which verifies the effectiveness of the optimized design method.